Cover Feature: Electropolymerization of Dithieno[3, 2‐b:2′, 3′‐d]arsole (ChemElectroChem 22/2018). Issue 22 (12th October 2018) - Imoto, Hiroaki; Yamazawa, Chieko; Hayashi, Shotaro; Aono, Masami; Naka, Kensuke
Abstract : The Cover Feature illustrates film fabrication via electropolymerization of dithieno[3, 2‐ b :2′, 3′‐ d ]arsole with the assistance of Lewis acid, BF3 . Dithienoheterole is an important backbone to incorporate heteroatoms into conjugated systems. This is the first example of the electropolymerization of dithienoheteroles. More information can be found in the Communication by H. Imoto et al. onpage 3357 in Issue 22, 2018 (DOI:10.1002/celc.201801069 ).